Validation of the PARC_CL 2.0 crack model for the assessment of the nonlinear behaviour of RC structures subjected to seismic action: SMART 2013 shaking table test simulation. (1st November 2017) - Belletti, B.; Stocchi, A.; Scolari, M.; Vecchi, F.
Highlights: The new PARC_CL 2.0 reinforced concrete model is proposed. PARC_CL 2.0 is applied to the analysis of a wall structure shaking table test. Local and global engineering demand parameters are evaluated. The proposed modelling provides results in agreement with the experimental data. Abstract: Presented in the paper is the new PARC_CL 2.0 crack model, a physical approach for RC modelling especially tailored to shear sensitive structures. The model is then applied for the seismic response assessment of the SMART 2013 specimen, a scaled RC nuclear power plants facility wall structure tested on a shaking table under strong seismic input. The aim of the research is to evaluate the predictive capacity of the modelling in terms of global and local response, in order to try to partially fill the gap for the need of non linear calculation for large structures and applicability of the modelling technique to the practice. The presented approach demonstrated to be able to provide satisfying results in terms of top displacement, floor acceleration spectra, interstorey drift and eigen frequency drop off. Moreover, the modelling using shell elements demonstrated to keep the amount of computational cost acceptable.